Formulation and Evaluation of Mouth Dissolving Tablets of Montelukast sodium - Chatterjee, Arindam; Vaghela, Bharat J.; Gupta, Rakesh Kumar; Ombir (Journal of Biomedical and Pharmaceutical Research, 2022)
The present study aims to formulate mouth dissolving tablets of montelukast sodium by direct compression method for the faster action, better absorption and improvement of bioavailability of the drug in management of Asthma. Total six formulations were developed with varying concentrations of combination of Crosspovidone and Sodium starch glycolate as super disintegrating agents. The tablets were prepared by direct compression method. The prepared MDT were evaluated for various parameters i.e. shape and size, weight variation, thickness, hardness, friability, wetting time, disintegration time, drug content, dissolution test, accelerated stability studies etc. After comparing the results (particularly disintegration time and dissolution profile), it was concluded that formulation TF3 was selected as the best formulation among all.Keywords: Montelukast sodium, Mouth Dissolving Tablets, Direct Compression, in-vitro dissolution.